The Suitable Factors for Lichtenberg Figures on Teak Wood Surface with DC High Voltage Source - Nernchad, Nattapong; Manosroi, Worapon; Phromfaiy, Apisak; Intuwong, Gunt (Frontiers in Engineering Innovation Research, 2022)
Nowadays, the teak furniture and products have increasing impact of the Thai economy system, therefore the waste of production process become increasing too. The objective of this research is developing the Lichtenberg wood burning machine with flyback transformer and analysis the appropriate factor for making Lichtenberg figures e.g., teak humidity, and the proportion between water and Sodium Carbonate. The result shows that the proportion of 200 ml of water and 5 G of NaHCO3 has significant most beautiful and best contrast to the Lichtenberg figures. Moreover, this research evaluated the innovation and technology by questionnaire is a pass IOC method. The results show that the innovation acceptance and the innovation and technology requirement have the average value of 4.71 and 4.60 respectively, which means a very high range. The efficiency of innovation and technology, innovation and technology manual and satisfaction with innovation and technology have the average value of 4.46, 4.50, 4.45 and 4.50 respectively which means a high range.